Prognostic implications of previously known or newly diagnosed diabetes and hypovitaminosis D in patients with myocardial infarction. (25th November 2020) - Aleksova, A; Santon, D; Stenner, E; Gagno, G; Francescut, C; Padoan, L; Saro, R; Beltrami, A.P; Sinagra, G
Abstract: Background: Vitamin D deficiency and diabetes mellitus are frequent among patients with acute myocardial infarction. Independently, both were associated with a worse prognosis after myocardial infarction (MI). However, it is unclear whether the risk of worse outcome, associated with diabetes mellitus, may be accentuated in presence of hypovitaminosis D. Purpose: We assessed if previously known or newly diagnosed diabetes is associated with worse outcome (major cardiovascular events) in combination with hypovitaminosis D in patients with acute MI. Methods and results: Were enrolled 1004 patients with acute MI; 64.7% of them, had hypovitaminosis D and 37% were diabetic. We grouped our population by diabetic status: previously known diabetes (diagnosis of diabetes before MI, n=330; 32.9%); newly diagnosed diabetes (during hospitalization for MI, but no known diabetes at presentation, n=47; 4.7%); or no diabetes (n=627; 62.5%). Hypovitaminosis D was more frequent among patients with previously known (70.2%) and newly diagnosed diabetes (73.3%), when compared to non diabetic patients (61.2%). During median follow-up of 15.6 months, patients with previously known and newly diagnosed diabetes had increased risks of major cardiovascular events (HR 1.72; 95% CI, 1.26 to 2.36. The risk of major events during the follow-up among diabetic patients, was further increased in presence of hypovitaminosis D (Figure 1). Conclusions: The presence of both, previously known or newly diagnosed diabetes and hypovitaminosis D, in patients with MI is synergistically associated with a worse outcome. Funding Acknowledgement: Type of funding source: None